2022
DOI: 10.3390/antibiotics11121785
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimycobacterial Activity of Human Lactoferrin-Derived Peptide, D-hLF 1-11, against Susceptible and Drug-Resistant Mycobacterium tuberculosis and Its Synergistic Effect with Rifampicin

Abstract: Tuberculosis is a highly contagious disease caused by the Mycobacterium tuberculosis complex (MTBC). Although TB is treatable, multidrug-resistant, extensively drug-resistant, and totally drug-resistant forms of M. tuberculosis have become a new life-threatening concern. New anti-TB drugs that are capable of curing these drug-resistant strains are urgently needed. The purpose of this study is to determine the antimycobacterial activity of D-enantiomer human lactoferricin 1-11 (D-hLF 1-11) against mycobacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Since it has recently been demonstrated that bacteria can develop resistance to AMPs and that their combined use allows to delay the evolution of pathogen resistance [ 8 , 9 ], the use of combined forms of lactoferrin-derived AMPs seems to be the most appropriate way to avoid the development of resistance. Such combinations can be based not only on AMPs or antibiotics [ 43 , 44 ], but also on enzymes that are active against different G(+) and G(−) bacteria [ 45 , 46 , 47 ]. In vitro studies of the combined use of various AMPs derived from human and bovine lactoferrin with traditional antibiotics revealed the presence of a synergistic effect between polypeptides and antibiotics; however, the obtained results were insufficient to produce therapeutic effects in vivo [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since it has recently been demonstrated that bacteria can develop resistance to AMPs and that their combined use allows to delay the evolution of pathogen resistance [ 8 , 9 ], the use of combined forms of lactoferrin-derived AMPs seems to be the most appropriate way to avoid the development of resistance. Such combinations can be based not only on AMPs or antibiotics [ 43 , 44 ], but also on enzymes that are active against different G(+) and G(−) bacteria [ 45 , 46 , 47 ]. In vitro studies of the combined use of various AMPs derived from human and bovine lactoferrin with traditional antibiotics revealed the presence of a synergistic effect between polypeptides and antibiotics; however, the obtained results were insufficient to produce therapeutic effects in vivo [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Colloidal silver, the dendritic amphiphile 3Cam19, the thiopeptide antibiotic NF1001 and the rifamycin derivate 5j reduced mycobacterial viability in established biofilms ( Falkinham et al, 2012 ; Paulowski et al, 2022 ; Feizi et al, 2023 ; Kaur et al, 2024 ). Finally, the antimicrobial peptide D-hLF-1–11, a derivate of lactoferrin, seemed to not affect M. abscessus biofilm biomass ( Intorasoot et al, 2022 ).…”
Section: Integrating Biofilm Techniques: Targeting the Myco...mentioning
confidence: 99%
“…Basically, LTF is an iron-chelating protein found in blood and bodily secretions, such as tears, sweat, and vaginal secretions [ 29 , 30 ]. In reference to its anti-biofilm property, LTF has been shown to have synergistic effects in combination with agents [ 31 ], such as AgNPs [ 27 ] and Xylitol [ 32 ], against biofilm-producing organisms. Since biofilm formers are also common pathogens associated with diabetic foot ulcers [ 22 ], combining AgNPs and LTF could potentially inhibit biofilm formation and eradicate bacteria that are living in diabetic wounds.…”
Section: Introductionmentioning
confidence: 99%